2021
DOI: 10.1109/access.2021.3073063
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Stability Analysis of the Conventional SRF-PLL and Enhanced SRF-EPLL

Abstract: Phase-locked loop (PLL) systems play a crucial role in grid synchronization. Since variations on the grid voltage parameters are in general uncertain, the dynamics of PLLs are by nature nonlinear. This fact imposes a relevant challenge to guarantee their stability. Unfortunately, as argued in this paper, there is a remarkable lack of global stability tests even for the most common approaches, such as the synchronous reference frame (SRF). In this case, there is only available a small-signal-linearized-modelbas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This does not change the system's orbits and, therefore, does not affect the comparison systems. The statement (15) then follows from (11).…”
Section: Autonomous Comparison Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…This does not change the system's orbits and, therefore, does not affect the comparison systems. The statement (15) then follows from (11).…”
Section: Autonomous Comparison Systemsmentioning
confidence: 99%
“…defined by (11) are called, respectively, the left and right autonomous comparison systems for (10). Remark 6.…”
Section: Autonomous Comparison Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3-ph inverter is either operated with SRF or droop control as per the grid available condition. The 3-ph inverter controller selection is done by islanding detection unit [4]- [6] which identifies the utility grid connection to the renewable micro-grid. The powers of the four renewable modules are utilized as per load demand and grid connection conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [28] suggests a linear active disturbance rejection control-based nonlinear PLL which improves the filtering capacity and the dynamic response during synchronization. A stability analysis based on Lyapunov's approach was conducted in Reference [29] and it was concluded that SRF-EPLL is asymptotically stable when the gain values are positive. A new synchronization method called decoupling network αβ frame PLL design is suggested in Reference [30].…”
Section: Introductionmentioning
confidence: 99%